School Adjustment and Socio-Family Risk as Predictors of Adolescents’ Peer Preference - Sánchez-Sandoval, Yolanda; Verdugo, Laura (Frontiers in Psychology, 2021)
This work analyzes peer preferences at the beginning of adolescence. For this purpose, each adolescent's sociometric status was studied in their classroom group and attempts were made to identify indicators of academic, personal, and socio-family adjustment related to that status. Participants were 831 adolescents studying 1st grade of Compulsory Secondary Education, in 31 classrooms from 10 schools. The 31 tutors of these students also participated. Sample selection was intentional. A quantitative research approach was used. Sociometric data were collected using the nomination method. Teachers provided information about these youths' adjustment and family risk variables. Descriptive analyses and bivariate correlations were calculated as a preliminary analysis of the study. Chi-square tests or ANOVAs examined the similarities and differences between status based on personal, socio-family, and school adjustment variables. Lastly, linear regression analysis and a Structural Equation Model (SEM) were performed. These latter analyses revealed that good performance and academic adjustment are important predictors of successful social relations. Also, the data show that the presence of personal and socio-family risk variables make it difficult for adolescents to be accepted by their peers. The results suggest the need for school and family support to promote peer acceptance. Working on both aspects can help improve classroom coexistence. Intervention techniques are recommended for the entire group, to intervene on attitudes, interpretations, and behaviors that enrich individual tools and the collective climate.